On teacher questioning: question-types in question - KESKES, Saïd (Journal of Human Sciences, 2006)
This paper, on collaborative research, purports to achieve teacher’s awareness raising on some teaching malfunctions pertaining to types of "Question" which might potentially affect teaching efficiency and pupils’ comprehension. Multiple interpretive accounts of data of teacher talk extracts (reported in Appendixes 1, 2, 3, and 4) are exploited for this purpose. This article does not seek to significantly provide any breakthrough on this particular aspect. It does not either purport to achieve generalisability or prove causal relationships. It simply attempts to realistically empower teacher’s with transcript-exploitation means, to appreciate, in the heat of their lesson deployment, whether the types of questions asked are pedagogically appropriate, in terms of comprehensibility, to create learning conditions. Learners’ reactions to these questions will serve as guiding-marks of pupils’ access to question comprehension.